O arrazoado por autoridade e a modalização discursiva: estratégias de argumentação no gênero projeto de pesquisa de TCC - Carvalho, Aleise Guimarães (2014)
Considering that the argumentation is inherent to the language and, consequently, to the discourse, we aim in this investigation to describe and analyze the argument by authority, one of the forms of polyphony of speakers, and the discursive modal verbs functioning as argumentative strategies in the genre Research Project of TCC. This is a genre of academic circulation and objectives to introduce undergraduate students in the sphere of scientific research. As theoretical approach we used the postulations of Ducrot (1987; 1988; 1997); Koch (2011), Nascimento and Silva (2012), Cervoni (1989) and Castilho and Castilho (1993); Bakhtin (2010), among others. The analysis of argument by authority and the modalization in the referred genre happen not only by the recurrence of these strategies, but also because we aim to observe how these two phenomena occur, concurrently, from the citations, in direct and indirect style, indicating the argumentation in the statements. This is a descriptive and interpretativist study, which corpus is constituted by sixteen (16) Research Projects of TCC: eight (8) from the Course of Licenciatura em Letras and the other eight (8) from the Bachelor Course of Secretariado Executivo Bilíngue. This research showed, during the analyzed corpus, that there is no difference in the speaker‟s commitment responsible for the text (L1) in relation to the discourse presented on direct and indirect style, in the genre Research Project of TCC. Independent of the employed style, L1 compromises with the discourse of the other speakers by presenting them in the form of argument by authority. Furthermore, the arguments by authority appear in concomitance with three different types of modal verbs: asseveratives; almost-asseveratives; evaluatives, with which L1 places in different way before the discourse of other speakers. Further, we verified the occurrence of arguments introduced by no modal terms. In the face of these, L1 only get compromised, but do not get responsible by the discourse of the other, and neither judjes him. Based on these evidences, we could verify that the Research Project of TCC is a polyphonic genre, rich in argumentative strategies.